Efektivitas Kebijakan Moneter Dalam Mengendalikan Inflasi di Indonesia dengan Pendekatan Error Correction Model (ECM) - Ningsih, Liasulistia; Tanjung, Indra Ismayudi (Journal of Business and Economics Research (JBE), 2025)
Inflation is one of the main problems facing Indonesia, and the effectiveness of policies in controlling inflation is still questionable because the findings of research analysis are still varied. Bank Indonesia as the central bank has made efforts to control inflation with various monetary policy instruments. Therefore, this study focuses on the effectiveness of monetary policy in controlling inflation in Indonesia. The data used in this study uses quarterly data covering the first quarter of 2010 to the fourth quarter of 2024. The research model used in this study uses the Error Correction Model (ECM) time series estimation. The results of the analysis found that interest rates and the amount of money in circulation as monetary policy instruments have not been effective enough in controlling inflation in both the short and long term. This is indicated by the results of the estimation of the significant but positive effect of interest rates on inflation in both the short and long term. While the amount of money in circulation has a significant negative effect in the long term and does not have a significant effect in the short term.